Antecedents and work-related correlates of reported sexual harassment: an empirical investigation of competing hypotheses. - Ragins, Belle Rose; Scandura, Terri A. (Sex Roles, 1995)
This study investigated antecedents and work-related correlates of reported sexual harassment by 365 primarily Caucasian women in male-typed, female-typed, and gender-integrated occupations. Two competing hypotheses on the antecedents of sexual harassment were tested. No support was found for the “contact hypothesis,” which holds that harassment is related to contact with the opposite gender. Partial support was found for the “sex role spillover” model, which holds that harassment is due to the transfer of gender roles to the workplace. No significant differences in reports of sexual harassment were found between women in male-typed, female-typed, and gender-integrated occupations. Within male-typed occupations, blue-collar women reported greater harassment than white-collar women, but were less likely to display assertive reactions to harassment. Investigation of work-related outcomes revealed that sexual harassment was positively related to reports of gender discrimination in promotion and employment practices, and had a negative impact on job satisfaction, particularly among blue-collar women. Theoretical implications of these results are discussed and a revision of the sex role spillover model is presented. Reprinted by permission of the author.